A Survey of Psychiatric Healthcare Workers' Perception of Working Environment and Possibility to Recover Before and After the First Wave of COVID-19 in Sweden - Alexiou, Eirini; Steingrimsson, Steinn; Akerstrom, Magnus; Jonsdottir, Ingibjörg H.; Ahlstrom, Linda; Finizia, Caterina; Wijk, Helle; Degl'Innocenti, Alessio (Frontiers in Psychiatry, 2021)
Objective. This study aimed to investigate the impact of the first wave of the COVID-19 pandemic on perceived working environment, including the possibility to recover, among psychiatric healthcare workers (PHCWs) in comparison with pre-pandemic measures. Method. A link to an anonymous, web-based COVID-19 related survey was sent via email to all PHCWs at Sahlgrenska University Hospital (Gothenburg, Sweden; n=1618) in September 2020. The response rate was 38% (566 of 1507 eligible participants). Working environment survey responses collected in 2019 were used as pre-pandemic comparators. Statistical analyses were performed to assess overall impact over time on work demands, support, motivation, and recovery, stratified by professional role, and considering variables such as access to personal protective equipment. Results. The percentage of individuals responding negatively to statements about working environment increased significantly for most items after the first wave. Registered nurses reported a greater negative impact of the pandemic on perceived working conditions and ability to recover than other professional groups. PHCWs working with patients with COVID-19 (35%) who reported being anxious about becoming infected (12%) or infecting others (17%), or lacking adequate personal protective equipment (22%) were more negatively impacted regarding work environment-related items than those who did not. Conclusions. PHCWs’ working environment and possibility for recovery were impacted by the first wave of the COVID-19 pandemic, nurses being most affected. Although psychiatric services do not directly care for patients with severe COVID-19 infection, the results from this study suggests that mental health services should also prepare for future pandemics.